Waktu Paparan Medan Magnet Extremely Low Frequency 300 ΜT Terhadap Daya Hantar Listrik Pada Proses Fermentasi Tempoyak - Ratna Ratna; Jumingin Jumingin; Atina Atina (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
This study aims to analyze the exposure time of the Extremely Low Frequency 300 μT magnetic field on the electrical conductivity of the tempoyak fermentation process. The research method is the experimental method. The research sample was divided into two groups, namely the control group which was not exposed to magnetic fields and the experimental group, namely the group that was given exposure to the Extremely Low Frequency 300 μT magnetic field with a time of 20, 40, and 60 minutes. The data obtained were analyzed by the F test, if the exposure time of the Extremely Low Frequency 300 μT magnetic field had a significant effect, then continued with the BNT test. The results showed that the electrical conductivity value in the experimental group was higher than the control group. The value of electrical conductivity in the control group is 1147 μS/cm, the value of electrical conductivity at 20 minutes exposure is 1156 μS/cm-1268 μS/cm, 40 minutes exposure is 1177 μS/cm 1275 μS/cm, and 60 minutes exposure is 1187 μS/cm-1331 μS/cm. The longer the exposure time to the 300 μT Extremely Low Frequency magnetic field, the higher the tempoyak electrical conductivity value. From the F test that has been carried out, it is found that the exposure time of the Extremely Low Frequency magnetic field significantly affects the value of the tempoyak electrical conductivity (FCount = 26,839 > FTabel = 4,76) with a significant 5%.